2017
DOI: 10.1016/j.tourman.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency analysis of major cruise lines

Abstract: h i g h l i g h t sThis study measured the efficiency of the top three cruise lines Network DEA and bootstrapped-truncated regression were used They were efficient at the operating stage, but varied at the non-operating stage Cruise lines attempting high capacity expansion were relatively inefficient Neglected hedging policy over financial risks also contributed to the inefficiency a b s t r a c t Three major cruise lines account for 82% of the total market share. Their financial statements show different resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 68 publications
1
25
0
2
Order By: Relevance
“…In addition, the profit of the system in the benchmark case when the total number of cruise tickets equals 0.6 is higher than the other cases with different total number of cruise tickets. In fact, it is not true that the larger the number of cruise tickets, the higher the profit of the system, because the system's profit has something to do with the total quantity of cruise tickets ordered by the two retailers; if the total number of cruise tickets is too larger, the total amount of cruise tickets ordered by the two retailers is not constrained by the total number of cruise tickets for the supplier, the operating costs are increasing, and then the efficiency of the system is lower, which is consistent with Parker and Kapuściński [6] and Chang and Lee et al [3]. The paper focuses on the difference of the expected profits of the cruise supply chain members and the system between them in the benchmark case and in the alliance case with a certain number of cruise tickets for the supplier; then we do not analyze the effect of the total number of cruise tickets for the supplier.…”
Section: Effects Of the Coefficients Andsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition, the profit of the system in the benchmark case when the total number of cruise tickets equals 0.6 is higher than the other cases with different total number of cruise tickets. In fact, it is not true that the larger the number of cruise tickets, the higher the profit of the system, because the system's profit has something to do with the total quantity of cruise tickets ordered by the two retailers; if the total number of cruise tickets is too larger, the total amount of cruise tickets ordered by the two retailers is not constrained by the total number of cruise tickets for the supplier, the operating costs are increasing, and then the efficiency of the system is lower, which is consistent with Parker and Kapuściński [6] and Chang and Lee et al [3]. The paper focuses on the difference of the expected profits of the cruise supply chain members and the system between them in the benchmark case and in the alliance case with a certain number of cruise tickets for the supplier; then we do not analyze the effect of the total number of cruise tickets for the supplier.…”
Section: Effects Of the Coefficients Andsupporting
confidence: 78%
“…According to Cruise Market Watch, the number of passengers is projected to grow to 25 million in 2019 with an average growth rate of 4.5% [3]. The substantial spending of cruise passengers, together with the high growth rates, indicates that the cruise industry has great market potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring the operating performance of a company is a complex process, requiring the measuring of numerous key indicators to ensure proper managerial decisions (Bagozzi & Phillips, 1982;Chakravarthy, 1986). The present study adopted multiple DEA input-output concepts and referenced the input-output variables used by other scholars (Chen & Chen, 2007;Chang & Chen, 2008;Chung, Lee, Kang, & Lai, 2008;Liu & Wang, 2008;Lu & Hung, 2010;Huang et al, 2014;Chang et al, 2017), proposing an evaluation model that can be used by corporate managers to maintain and improve their company performance. A literature review clearly showed that conventional and two-stage DEA differ with respect to the performance evaluation process.…”
Section: Performance Evaluation Frameworkmentioning
confidence: 99%
“…However, the conventional approach overlooks intermediate products and linking activities and thus fails to present adequate management messages during the production process. In this context, subsequent scholars began to adopt two-stage production procedures for measuring operating performance in various industries (Seiford & Zhu, 1999;Zhu, 2000;Luo, 2003;Sexton & Lewis, 2003;Chen & Zhu, 2004;Kao & Hwang, 2008;Lu & Hung, 2011), including the CCI (for an example, Chang, Lee, & Park, 2017).…”
Section: Introductionmentioning
confidence: 99%